THE INFLUENCE OF ADDITIVE BASED ON GLUCOSE ON THE SETTING TIME AND STRENGTH OF DRILLING CEMENT: PENGARUH PENAMBAHAN ADITIF BERBAHAN DASAR GLUKOSA TERHADAP SETTING TIME DAN STRENGTH SEMEN PEMBORAN - Resesiyanto, Hastowo; Setyowati, Riris (INTAN Jurnal Penelitian Tambang, 2025)
Oil well cement is a cement commonly used in the petroleum industry, especially in cementing operations. This cement is a type of Portland cement and is anhydrous, meaning that the components in the cement will break up and form hydrate components when meeting water and then slowly harden. In the preparation of cement suspensions and during cementing operations, the physical properties of cement suspensions must always be considered because they will affect the quality of cementing results. Research was conducted on a laboratory scale based on experiments to test the physical properties of drilling cement. The experiment aims to test the compressive strength of cement rock and the setting time in the form of initial and final setting time required by the cement suspension to harden as a result of the addition of glucose-based additives. The test results showed that the greater the concentration of glucose-based additives added to the drilling cement suspension, the longer the setting time of the cement suspension and the lower the strength of the cement rock.